FACULTY AND GRADUATES ON STUDENT ASSESSMENT SYSTEMS IN THE INITIAL TRAINING OF PRESCHOOL TEACHERS - Martínez Mínguez, Lurdes (2014)
In view of the need to improve course descriptions, the most recent graduate classes of initial training of Preschool Teachers at Universidad Autónoma de Barcelona have been studied in order to gain insight on the status of the student assessment systems. The methodology used was qualitative using focus groups of teachers and graduates of the last four classes (2007-2011). The results show similar perceptions regarding coherence among the different course program items and the transparency of the assessment methods applied. Some different perceptions have been noticed in respect to the instruments used, the feedback provided and the cognitive abilities more frequently assessed. The study concludes that it is essential that all teaching guides show coherence in the various items; that the students have an early knowledge of the assessments, in a clear and transparent manner; that self and co-evaluation systems are included; and that the faculty guide the connection between theory and practice in a critical and reflexive way.